Bromodomain 4 is a potent prognostic marker associated with immune cell infiltration in breast cancer. Issue 1 (7th September 2020) - Zhong, Limei; Yang, Zhiyong; Lei, Da; Li, Lijuan; Song, Shaohua; Cao, Donglin; Liu, Yufeng
Abstract: Bromodomain 4 (BRD4), a member of the bromodomain and extra‐terminal domain protein family, has become a promising epigenetic target in cancer and inflammatory diseases; however, the detailed biological role of BRD4 in breast cancer (BRCA) remains undetermined. We analysed the BRD4 expression levels using the Oncomine and TIMER databases and evaluated the clinical impact of BRD4 on BRCA prognosis using Kaplan‐Meier plot and PrognoScan. The correlation between BRD4 and tumour‐infiltrating immune cells was investigated using TIMER. Furthermore, the correlation between BRD4 expression levels was also analysed using TIMER in addition to the GEPIA database for immune cell gene markers. BRD4 expression was significantly higher in BRCA tissues than in normal tissues, which was significantly correlated with poor overall survival (OS). Specifically, high BRD4 expression was correlated with worse OS and progression‐free survival in patients with BRCA. In addition, BRD4 expression was correlated with levels of infiltrating monocytes (CSF1R, cor = 0.204, P  = 9.19e−12), tumour‐associated macrophages (CD68, cor = 0.129, P  = 1.81e−05), M1/M2 macrophages and different effector T cells (including Th1/Th2/Treg) in BRCA. These findings suggest that BRD4 could be used as a prognostic biomarker for determining prognosis and immune cell infiltration levels in BRCA.